PENGUKURAN KINERJA BERDASARKAN BALANCE SCORECARD PADA PT.BPR NUSANTARA BONA PASOGIT 9 PANGURURAN - Malau, Timorencis (UNIKA Santo Thomas, 2012)
This study aims to determine how the performance of the archipelago PT.BPR Bona Pasogit 9 Pangururan if measured by the Balanced Scorecard method. Population in this research is the financial reports, customer data, customer data and employee data that complaints were trained on the archipelago PT.BPR Bona Pasogit 9 Pangururan since its establishment in 1991 to the year 2011. The study sample-2011.Data 2010 data used in this study is documentation techniques. Techniques of data analysis in this research is descriptive method. From the results of research and discussion, it can be concluded that the measurements made during this performance only aims to increase financial performance. It can be seen from the measuring instruments used by the company so far in measuring their performance is to increase profits. Non-financial performance is not included in the performance measurement used, so that the resulting performance is inadequate. It can be seen from the increase in the level of customer complaints, lessons given to employees in order to improve the quality of employees is less well programmed. It is recommended to apply the balanced scorecard system to measure the performance of the company, so the goal PT.BPR archipelago Bona Pasogit 9 financial and non-financial Pangururan can be achieved to improve the ability of the company over the competition